Jual Beli Emas Secara Kredit pada Produk BSI Cicil Emas Perspektif Maqasid Syari'ah - Ittasyaq, Nurul Laili (Fakultas Ekonomi dan Bisnis Islam UIN Raden Mas Said Surakarta, 2025)
Non-cash gold transactions such as the BSI Gold Installment product have gained increasing popularity as an accessible form of gold investment. Nevertheless, installment-based gold trading raises fiqh concerns, as gold is classified as a ribawi commodity that should be exchanged on a spot basis (yadan bi yadin). This study aims to examine the compliance of the BSI Gold Installment scheme with Maqasid Shariah. Using a qualitative descriptive-analytical approach, this study relies on secondary data derived from official BSI product documents, Islamic jurisprudence literature on gold transactions, and relevant DSN-MUI fatwas. The data were analyzed through qualitative data reduction and conclusion drawing. The findings indicate that the use of a murabahah contract in the BSI Gold Installment product is generally permissible in non-cash gold transactions. From a Maqasid Shariah perspective, this product supports hifz al-mal (the preservation of wealth) by facilitating access to gold investment. However, this objective requires transparency in pricing, prior ownership of the gold by the bank before resale, and clear delivery mechanisms to avoid gharar and ensure full compliance with Shariah principles.